Odpowiedź :
skoro masz wzór podstawiasz do niego zamiast x te Twoje dane
i tak:
y=-x+1
x=-2
y=--2+1=2+1=3
x=-1
y=--1+1=1+1=2
x=0
y=0+1=1
x=1
y=-1+1=0
x=2
y=-2+1=-1
Pozdrawiam:)
i tak:
y=-x+1
x=-2
y=--2+1=2+1=3
x=-1
y=--1+1=1+1=2
x=0
y=0+1=1
x=1
y=-1+1=0
x=2
y=-2+1=-1
Pozdrawiam:)
Po prostu podstawiasz do wzoru :)
x=-2
y=-(-2)+1
y=2+1
y=3
x=-1
y=-(-1)+1
y=1+1
y=2
x=0
y=0+1
y=1
x=1
y=-1+1
y=0
x=2
y=-2+1
y=-1
x=-2
y=-(-2)+1
y=2+1
y=3
x=-1
y=-(-1)+1
y=1+1
y=2
x=0
y=0+1
y=1
x=1
y=-1+1
y=0
x=2
y=-2+1
y=-1